Grow triploid cultivars of Nagpur mandarin for better harvest - Narukulla, Vijayakumari; Krishnani, Pooja (Indian Horticulture, 2019)
The scientist have successfully regenerated a few plantlets via somatic embryogenesis from endosperm tissue of Nagpur mandarin. The ploidy level of all plants is to assessed through cytogenetic techniques/ flow cytometry and confirmed triploids are transferred to greenhouse by shoot tip grafting/ microbudding. Further, experiments are continued to increase regeneration by modifications in growth media and by taking up controlled pollinations. The initial results from study demonstrated the feasibility of plantlet regeneration from hybrid endosperm (natural triploid tissue) of Nagpur mandarin, a single step approach to triploid seedless production.